2021
DOI: 10.1186/s40981-021-00461-9
|View full text |Cite
|
Sign up to set email alerts
|

Urgent surgery for COVID-19–positive pediatric patient

Abstract: Background We present a case of COVID-19–positive pediatric patient for urgent urological surgery by spinal anesthesia to avoid aerosolizing procedure. Case presentation A 12-year-old, COVID-19–positive boy presented for urgent wound incision and drainage at the circumcision site. Our anesthetic plan consisted of spinal anesthesia with sedation. He was transported from the COVID-19 isolation floor to the negative pressure operating room. He was pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Basnet et al advocated for conservative management of acute appendicitis in infected children as a safer alternative for treatment 17 . A case report described spinal anesthesia as a safe alternative to general tracheal anesthesia in certain contexts of pediatric surgery to avoid the risks of infection to staff and pulmonary injury to patients 18 . However, Matava determined that endotracheal intubation may be performed safely on infected patients with proper precautions 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Basnet et al advocated for conservative management of acute appendicitis in infected children as a safer alternative for treatment 17 . A case report described spinal anesthesia as a safe alternative to general tracheal anesthesia in certain contexts of pediatric surgery to avoid the risks of infection to staff and pulmonary injury to patients 18 . However, Matava determined that endotracheal intubation may be performed safely on infected patients with proper precautions 19 .…”
Section: Discussionmentioning
confidence: 99%
“…He was placed in a lateral decubitus position and oxygen was delivered through a facemask. Under sedation, spinal anesthesia was achieved at the first attempt as a safe alternative to general endotracheal anesthesia [65].…”
Section: Circumcision and Covid-19mentioning
confidence: 99%
“…2, 3 However, both anesthesiologists and surgeons have traditionally been reluctant to apply SpA in the pediatric population. 4 A survey study revealed that the unwillingness to apply SpA for routine pediatric surgical procedures is multifactorial in nature. One factor that possibly contributes to such reluctance among surgeons may be the idea that SpA is technically difficult and entails a longer preoperative time.…”
Section: Introductionmentioning
confidence: 99%